If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32x + -12 = -18 Reorder the terms: -12 + 32x = -18 Solving -12 + 32x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 32x = -18 + 12 Combine like terms: -12 + 12 = 0 0 + 32x = -18 + 12 32x = -18 + 12 Combine like terms: -18 + 12 = -6 32x = -6 Divide each side by '32'. x = -0.1875 Simplifying x = -0.1875
| X+3=5+4 | | ln(3x+1)=-4 | | 27000*x-0,5=10000*x | | 14(X)+48(1-X)=47.5 | | 78(X)+47(1-X)=47.7 | | 16y-20=60-4y | | 0.4x+16.5=x-1.62 | | X=Z-(X*Y) | | x=(x-1)(1.075) | | 9x+2y=192 | | 2x^2+4x+21=0 | | x^2+25x-259=0 | | 10x+8=8x+2 | | 9x+9=9x+1 | | 20x+9=7x+1 | | 2/3j=-12 | | 3/4j=-12 | | 3x+2=1x+7 | | 14x+1=4x+2 | | r=x*(0.6-x)*(1.2-x) | | 10x+3=4x+9 | | 5x-2=1x+7 | | 3x^3=8+x | | 3x^2+3x+23=0 | | (9-8x)(8x+9)-72=x(4-60) | | 2x=20-14 | | 5w-3y+7=0 | | 2x+6-6=24-6 | | (2x-3)/(2=x-6)/3 | | 5x+4-4=29-4 | | 3x+4-4=28-4 | | x+(x*0.1)=218 |